Revisiting Curriculum 2013: Challenge the Potential Obstacles, Efficacy, and Effectiveness of Former Curriculum in Indonesia - Mutia Rosiana Nita Putri (Education Specialist, 2023)
Curriculum changes invariably spark debate, often with proponents and opponents. Before the implementation of the Merdeka Curriculum, the initial deployment of Curriculum 2013 in Indonesia raised concerns among many school teachers nationwide. Revisiting the former curriculum tends to offer benefits in predicting new curriculum implementation in Indonesia. This study employs a narrative review style to examine various relevant academic publications and data from the Programme for International Student Assessment (PISA). The data analysis process, including data selection, presentation, and findings, is conducted using the Miles and Huberman methodology. In conclusion, I argue that Curriculum 2013, as a response to a series of weaknesses in Indonesia's education system, has the potential to enhance learning outcomes. However, it necessitates significant reforms in a complex socio-demographic country like Indonesia, particularly in terms of assessment, pedagogy, and the readiness of students, teachers, and schools. Concerning potential obstacles to implementing such a curriculum, challenges arise from teacher readiness, student readiness, and school preparedness, including material provision such as books, as well as difficulties in assessing and implementing pedagogy